Behaviour, Attitudes and Knowledge of Healthcare Workers on Breastfeeding - Marija Čatipović; Zrinka Puharić; Drita Puharić; Paula Čatipović; Josip Grgurić (MDPI AG, 2022)
The aim of this paper is to determine the current state of behavior, attitudes, and knowledge of health professionals about breastfeeding in Croatia. Data were collected via a breastfeeding behavior, attitudes, and knowledge questionnaire, which has already been validated and used in Croatia. The secondary aim is to identify differences in outcomes of respondents by occupation (nurses versus others health professionals). In the study, 374 health professionals participated (37 males and 337 females). Respondents completed the questionnaire online. Respondents were rarely involved in breastfeeding education. On the behavior scale, the worst answer was given to the question of advising mothers on breastfeeding after 24 months. On the attitude scale, the worst result was achieved in terms of public breastfeeding and the support of the child's father for the breastfeeding mother. Respondents demonstrated the worst knowledge of The International Code of Marketing of Breast-milk Substitutes and the use of medications while breastfeeding. There was no statistically significant difference between the results of respondents in relation to the occupation of the respondents. In the preparation of future breastfeeding education for health professionals in Croatia, particular attention should be given to these issues.